Epidemiological analysis of axillary apocrine bromhidrosis in China: a survey from Chinese higher education students - Zhang, Lei; Cheng, Jiaqi; Wang, Cangyu; Zhao, Junhong; Zhang, Cuiping; Li, Haihong (Frontiers in Medicine, 2023)
Background There are few epidemiological data on axillary apocrine bromhidrosis (AAB) in the Chinese population, making it impossible to accurately estimate its prevalence or impact on individuals. Objective To estimate the prevalence of AAB in China, and to survey and compare the psychological status of individuals with and without AAB. Methods Students in several universities in China were surveyed online for AAB, and the prevalence of AAB was calculated. The Symptom Checklist 90 (SCL-90) was used to evaluate the psychological status. Results The prevalence of AAB in the surveyed students was 7.5% (194/2571). The projected number of Chinese higher education students with AAB was about 3 million. The onset age of AAB was mainly between 11 and 20 years old (79.90%, 155/194). 68.04% (132/194) of individuals with AAB had a positive family history, and 60.30% (117/194) had wet earwax. Individuals with AAB often felt depression, anxiety, loneliness and social alienation, and scored significantly higher on the nine primary psychological symptom dimensions than individuals without AAB. Conclusion AAB affects a small proportion but large numbers of Chinese population. China and the West or East-Asia and the West have different perception, recognition and treatment preferences for AAB.